How to make climate-neutral aviation fly - Romain Sacchi; Viola Becattini; Paolo Gabrielli; Brian Cox; Alois Dirnaichner; Christian Bauer; Marco Mazzotti (Nature Communications, 2023)
Abstract The European aviation sector must substantially reduce climate impacts to reach net-zero goals. This reduction, however, must not be limited to flight CO2 emissions since such a narrow focus leaves up to 80% of climate impacts unaccounted for. Based on rigorous life-cycle assessment and a time-dependent quantification of non-CO2 climate impacts, here we show that, from a technological standpoint, using electricity-based synthetic jet fuels and compensating climate impacts via direct air carbon capture and storage (DACCS) can enable climate-neutral aviation. However, with a continuous increase in air traffic, synthetic jet fuel produced with electricity from renewables would exert excessive pressure on economic and natural resources. Alternatively, compensating climate impacts of fossil jet fuel via DACCS would require massive CO2 storage volumes and prolong dependence on fossil fuels. Here, we demonstrate that a European climate-neutral aviation will fly if air traffic is reduced to limit the scale of the climate impacts to mitigate.